Explanation of the use of ozonated stem cells of cord blood - A. В. Kebkalo (Zaporozhye State Medical University, 2013)
Introduction. Experimental studies using stem cells of cord blood were conducted on mature guinea pigs with the model of pancreatic necrosis. The results are presented in the article "Changes in the blood physical state regulation of guinea pigs with the model of pancreatic necrosis". The influence of ozonated stem cells transplantation of cord blood on the intensity of plasma proteolysis was studied and the results of guinea pigs lethality with pancreatic necrosis are given in the paper. Taking into consider the results of the performed experimental studies, we came to the conclusion that the most indicative results are present in the group of animals using ozonated stem cells. 2. Objective of the research To prove the applying expediency of cord blood cells ozonation. 3. Materials and methods. Suspension of stem cells after 30 minutes of staying in ozonated saline was studied to determine the efficacy of ozone using with the view of activating stem cells. Ozonation of cord blood stem cells suspension was performed by mixing 1.0 ml of ozonized (apparatus "Ozone UM-80") sterile 0.9% solution of sodium chloride with 1.0 ml of cell suspension, with the concentration of ozone in isotonic sodium chloride 20 mg/1 ml. In blood we determined levels of free and protein associated oxyproline, hexosamines, hexuronic acids, fucose not associated with proteins, sialic acids and lytic collagen activity of plasma. The research was conducted among patients with necrotizing pancreatitis. Patients were divided into 2 groups: patients of first group received standard treatment (20 people), the second group consisted of 20 patients, whom ozonized saline was injected intravenously postoperatively. Besides, 25 healthy individuals (blood donors) were examined for the control. All the patients were inspected before surgical intervention and on the third and seventh day after surgery. 4. Results and discussion. Activation of cord blood stem cells with ozone increases the potential of transplantation through increased colony-forming factors per 1.66 (p<0.05) times while saving the same total number of nucleated blood cells, mononuclear in exfusate and preserving their viability. Taking mentioned above and the results of experimental studies into account we consider it appropriate to use ozonation of stem cells of cord blood in the clinic for more effective influence on the reparative processes. 5. Conclusions. 1. The use of ozonized saline solution in the complex treatment of patients with necrotizing pancreatitis didn't lead to significant intensification of reparative processes and data of metabolic connective tissue wasn't significantly different from the group of patients with standard treatment. 2. Activation of stem cells of cord blood by ozone leads to increase in transplant potential by increasing colony-forming factors, while keeping the total number of nucleated blood cells, mononuclear cells in exfusate and preserving their viability. 3. Taking mentioned above and data of experimental research into account, we consider it appropriate to use ozonation of cord blood stem cells in the clinic for their effective influence on the reparative processes.